Pathology Survey on a Captive-Bred Colony of the Mexican Goodeid, Nearly Extinct in the Wild, Zoogoneticus tequila (Webb & Miller 1998) - Alessio Arbuatti; Leonardo Della Salda; Mariarita Romanucci (The Scientific World Journal)
The Mexican Goodeid, Zoogoneticus tequila, is considered nearly extinct in the wild and it is maintained in captivity by the nonprofit international “Goodeid Working Group.” The unique Italian colony has produced about 180 fish so far. The observable diseases were registered and some fish were submitted, immediately after spontaneous death, to necroscopic and histopathologic exams. Encountered diseases included the following: 7 cases of scoliosis (2 males and 5 females); 2 fish with a similar congenital deviation of ocular axis; 1 adult male with left corneal opacity, presumably of traumatic origin; 1 female fish with a large subocular fluid-filled sac, histologically referable to a lymphatic cyst, similarly to the eye sacs of a Goldfish variety (Carassius auratus) called bubble eye; and 1 female fish with recurrent abdominal distension consequent to distal bowel dilation and thinning, associated with complete mucosal atrophy, and comparable to intestinal pseudo-obstruction syndromes described in humans and various animal species. The absence of infectious or parasitic diseases, as well as the low incidence of diseases potentially related to environmental alterations or nutritional disorders such as spinal deformities, suggests the adequacy of breeding management techniques of Z. tequila for its conservation and reintroduction in to the original habitat in the near future.